Keterampilan Interpersonal dan Work Readiness Mahasiswa Tingkat Akhir Universitas Kristen Satya Wacana menuju Industri 5.0 - Lidwina Jovian Dwi Ariesta; Sutarto Wijono (EduInovasi: Journal of Basic Educational Studies, 2025)
Technological development toward the industry 5.0 era requires university graduates to have work readiness that is not only focused on technical skills, but also on interpersonal skills as part of human-centered soft skills. Final-year students are in a transition from academic life to the professional life, making work readiness an important factor in facing job market dynamics and competition. This study aims to examine the relationship between interpersonal skills and work readiness among final-year students of Satya Wacana Christian University. This study used a quantitative approach with a correlational design involving 97 final-year students who were completing their undergraduate thesis. The research instruments consisted of the Interpersonal Skills Scale and the Work Readiness Scale. Data were analyzed using Pearson Product Moment correlation. The results showed a positive and significant relationship between interpersonal skills and work readiness (r = 0.338; p < 0.05). These findings indicate that interpersonal skills play an important role in improving students’ work readiness in the industry 5.0 era.